2015
DOI: 10.1177/1468087415603005
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-made fuels for future engine concepts

Abstract: Increasing carbon dioxide accumulation in earth's atmosphere and the depletion of fossil resources pose huge challenges for our society and, in particular, for all stakeholders in the transportation sector. The Cluster of Excellence 'Tailor-Made Fuels from Biomass' at RWTH Aachen University establishes innovative and sustainable processes for the conversion of whole plants into molecularly well-defined fuels exhibiting tailored properties for low-temperature combustion engine processes, enabling high efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 20 publications
4
105
0
1
Order By: Relevance
“…Furthermore, 2-MF exhibited a higher vapor pressure, a lower heat of vaporization and a better primary droplet breakup than ethanol. The results indicated that the combustion stability of 2-MF can result in higher knock resistance than gasoline [164][165][166]. At a higher compression ratio, an efficiency increase of up to 19% could be achieved with 2-MF compared to gasoline [164][165][166].…”
Section: Engine Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, 2-MF exhibited a higher vapor pressure, a lower heat of vaporization and a better primary droplet breakup than ethanol. The results indicated that the combustion stability of 2-MF can result in higher knock resistance than gasoline [164][165][166]. At a higher compression ratio, an efficiency increase of up to 19% could be achieved with 2-MF compared to gasoline [164][165][166].…”
Section: Engine Studiesmentioning
confidence: 96%
“…A number of engine studies of individual pure furans investigated the performance of 2-MF [18,[163][164][165][166]. Thewes et al [163] investigated the impact of using 2-MF on engine performance and in-cylinder spray evaporation and formation in a direct-injection spark-ignition (DISI) single-cylinder research engine.…”
Section: Engine Studiesmentioning
confidence: 99%
“…Traditionally for this conference series, one session deals with new aspects of measurement techniques and another one with modeling and numerical simulations. Five of the contributions have been presented in the form of invited keynote lectures, four of them reviewing aspects of diesel engine design by Miles and Andersson, 2 fuels for future engine concepts by Hoppe et al, 3 scale-resolving simulations (SRS) using high power computation resources for engine combustion by Hasse 4 and of SI engine development by Spicher and Magar. 1 In an additional keynote lecture, the new 3-cylinder TwinPower turbo gasoline engine inside the i8 hybrid car from BMW has been introduced.…”
Section: Th International Congress Of Engine Combustion Processes: mentioning
confidence: 99%
“…1 The first three review papers mentioned are also included in this Special Issue. [2][3][4] This Special Issue is a selection of 13 papers presented at the ENCOM congress covering several different aspects within the broad range of engine combustion. Only those papers have been selected and submitted for peer review in the International Journal of Engine Research which promise to provide new information in the field or which own at least in some aspects a review-like character.…”
Section: Th International Congress Of Engine Combustion Processes: mentioning
confidence: 99%
“…Proceeding this way for every emerging molecular biofuel structure is timeconsuming and-given the multitude of possible structuresmay not lead to systematic improvements.H erein, we propose to assess the process chain in the reverse direction, by using the requirements of the engine environments and the understanding of the combustion processes as design criteria to identify suitable molecular structures for fuel candidates as synthetic targets. [50] In Section 2, we will describe the current status,from which one can derive some general requirements for fuels that could foreseeably be used in ground transportation. In Section 3, ac oncise introduction will be given into conventional and modern engine concepts to appreciate the resulting criteria for tailor-made fuels.T his section will cover the most important aspects and issues of relevance to biofuel design along the sequence from the macroscopic thermodynamic process via the mesoscopic injection, mixing, and fuel break-up processes to the microscopic molecular reactions that-jointly-determine efficiency, that is,C O 2 release from combustion, and emissions.F rom consideration of these requirements,c ertain lead structures for cellulosic biofuels are emerging,w hich will be discussed in Section 4 together with their production.…”
Section: Introductionmentioning
confidence: 99%